Protection of the texts using Base64 and MD5 - Taha, Imad; Alahmad, Mohammad; Ahmad, Hanadi (Design for Scientific Renaissance, 2012)
The encryption process combines mathematics and computer science. Cryptography consists of a set of algorithms and techniques to convert the data into another form so that the contents are unreadable and unexplainable to anyone who does not have the authority to read or write on these data. The main objective of the use of encryption algorithms is to protect data and information in order to achieve privacy. This paper discusses an encryption method using base64, which is a set of encoding schemes that convert the same binary data to the form of a series of ASCII code. Also, The MD5 hash function is used to hash the encrypted file performed by Base64. As an example for the two protection mechanisms, Arabic letters are used to represent the texts. So using the two protection methods together will increase the security level for protecting the data.